Beyond Centers and Circle Time Learning Management in TK Intan Permata Aisyiyah Makamhaji - Sari, Tira Lapan (Early Childhood Research Journal (ECRJ), 2021)
This study aims to describe 1) planning of learning centers at TK Intan Permata, 2) implementing learning centers and evaluation of learning centers. This research is a qualitative descriptive study. Collecting data using interview and documentation methods. Interviews are used to collect data on planning, implementation and evaluation of learning. Documentation in the form of files as supporting data for interview results. The data sources of this research are center teachers, class teachers and school principals. The data validation used source and technique triangulation. Data analysis used interactive analysis model of Miles and Huberman with data reduction steps, data display, and conclusions. The results showed: 1) Learning planning by making types of planning. The types of planning are annual programs, semester programs, RPPM and RPPH. The lesson planning refers to the school curriculum but the content of the material is not based on the needs of the child. 2) Center learning is a part of the whole one day learning. For the implementation of the learning process, the children come with the class teacher, then the center teacher then goes home. The central learning procedure includes the footing of the playing environment, the footing before playing, the footing when playing and the footing after playing. The pattern of moving the center, every day the children take turns the teacher stays. Periodic shift of centers. The teacher has a position as a center teacher as well as a class teacher, 3) The aspect that is evaluated is the stages of child development by referring to STTPA. Evaluation is carried out by conducting an assessment. The assessment is carried out in stages, namely daily, weekly, monthly, and once a semester. Evaluation results are used only for LPPA to parents.Keywords : planning, implementation, evaluation